Organic mechanophosphorescent material based on phenoselenazine derivative as well as preparation method and application of organic mechanophosphorescent material
The preparation of organic force phosphorescent materials through phenselenazine derivatives solves the problem of insufficient brightness and durability of existing materials, and achieves efficient force-luminescence performance, which is applied to stress detection, ultrasonic luminescence and underwater ultrasonic detection.
Patent Information
- Application Number
- CN202510439527.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2025-07-11
AI Technical Summary
Existing organic electroluminescent materials have shortcomings in brightness, recovery and durability, limiting their applications in biomedical, optoelectronics, and energy fields.
The organic ferrophosphorescence material is prepared by using phenselenazine derivatives. By reacting with 4-bromo-4'-fluorobenzophenone, a crystal of ferrophosphorescence material with high phosphorescence efficiency is prepared, and it is applied to a composite film. The regular arrangement of crystalline materials is optimized by molecular interactions to produce a piezoelectric effect.
It has achieved efficient force-induced luminescence performance, expanded the application range of stress detection, ultrasonic luminescence and underwater ultrasonic detection, and the phosphorescence efficiency reaches 61.4%, which is the highest value in the existing force-induced luminescence system.
Smart Images

Figure CN120289379A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of organic mechanoluminescent materials, and particularly relates to a highly efficient organic mechanoluminescent material based on phenoselenazine derivatives and its applications. Background Art
[0002] Mechanoluminescence (ML) refers to the luminescence phenomenon generated when a material is stimulated by mechanical forces (such as pressure, strain, or friction). Since mechanical forces are ubiquitous in nature, mechanoluminescent materials have broad application prospects in the fields of biomedicine, optoelectronics, energy, and environmental science. It is worth noting that, in addition to traditional contact excitation, mechanoluminescence can also be induced by non-contact forces such as ultrasonic waves, which provides a new technical approach for non-invasive diagnosis in medical imaging and treatment. In recent years, researchers have been committed to developing mechanoluminescent materials with high brightness and high stability to meet the actual application requirements. Currently, mechanoluminescent materials mainly include inorganic crystals, metal-organic frameworks, perovskites, and organic crystals. Among them, organic mechanoluminescent materials have attracted much attention due to their low cost, adjustable structure, simple preparation, and rich luminescence properties.
[0003] However, compared with inorganic mechanoluminescent materials, organic mechanoluminescent materials still have deficiencies in terms of brightness, recoverability, and durability, which to a certain extent limit their development. So far, the research has mainly focused on the instantaneous mechanofluorescence caused by the radiative transition from the singlet excited state to the ground state. Summary of the Invention
[0004] The purpose of the present invention is to solve the above problems and propose an organic mechanoluminescent material based on phenoselenazine derivatives and its preparation method.
[0005] Another purpose of the present invention is to provide the applications of the organic mechanoluminescent material based on phenoselenazine derivatives. This material can be effectively applied to stress detection, ultrasonic luminescence, underwater ultrasonic detection, and other scenarios.
[0006] The purpose of the present invention is achieved by the following means:
[0007] An organic mechanoluminescent material based on phenoselenazine derivatives has a structure shown in formula (I):
[0008]
[0009] Wherein, -X- is one of -O-, -S-, -Se-, -Te-, or -SO2-; each of R1 to R7 is independently selected from any one of F, Cl, Br, I, and -CH3.
[0010] Preferably, the -X- is selected from one of -O-, -S-, -Se-, -Te- or -SO2-, R1, R2, R4, R5, R6, R7 are each independently selected from -CH3, and the R3 is selected from any one of F, Cl, Br, I.
[0011] More preferably, the -X- is selected from -Se-, R1, R2, R4, R5, R6, R7 are each independently selected from -CH3, and the R3 is selected from any one of F, Cl, Br, I.
[0012] Most preferably, the molecular chemical formula of the above-mentioned mechanoluminescent material is as follows:
[0013]
[0014] The preparation steps of the above compound are as follows:
[0015] Weigh phenoselenazine and sodium tert-butoxide and place them in a two-necked flask. After sealing, evacuate and refill with nitrogen. Then add N,N-dimethylformamide as a solvent and stir the reaction at room temperature. Next, under nitrogen protection, transfer the mixed solution to a reaction flask containing 4-bromo-4'-fluorobenzophenone and react at 100 °C. After the reaction is completed, extract with dichloromethane, and then separate and purify by column chromatography to obtain a crude product. Finally, obtain the crystal of the mechanoluminescent material by recrystallization.
[0016] Preferably, in the above steps, the mixed solution reacts with 4-bromo-4'-fluorobenzophenone for 11 - 13 hours; phenoselenazine and sodium tert-butoxide are stirred and reacted at room temperature for 2 - 3 hours. More preferably, the mixed solution reacts with 4-bromo-4'-fluorobenzophenone for 12 hours; phenoselenazine and sodium tert-butoxide are stirred and reacted at room temperature for 2 hours.
[0017] Preferably, the molar ratio of phenoselenazine, sodium tert-butoxide to 4-bromo-4'-fluorobenzophenone is 3.9 - 4.1:7.9 - 8.1:4.1 - 4.2. Most preferably, the molar ratio of phenoselenazine, sodium tert-butoxide to 4-bromo-4'-fluorobenzophenone is 3.98:8.01:4.19.
[0018] The above-mentioned organic mechanoluminescent material can be applied in stress detection, sonoluminescence and underwater ultrasonic detection.
[0019] The above-mentioned organic mechanoluminescent material can be used to prepare a composite film, and good ultrasonic signal collection can be achieved underwater by using this composite film.
[0020] The composite film prepared by using the above-mentioned organic mechanoluminescent material is prepared by the following method:
[0021] In poly(butylene adipate-co-terephthalate) (PBAT), dichloromethane was added as a dispersion solvent. After ultrasonic treatment and stirring, a clear solution was obtained. Then, the crystals of the above-mentioned mechanoluminescent material were weighed and added to the solution, and stirred to ensure uniform dispersion. After heating the obtained mixture to volatilize dichloromethane, a composite film of polymer-coated compound molecules was obtained.
[0022] Preferably, the mass ratio of the mechanoluminescent material crystals to poly(butylene adipate-co-terephthalate) is 1:10 - 11, and the mass ratio is further preferably 1:10.
[0023] The mechanoluminescent molecules of the present invention have a large molecular dipole moment and a non-centrosymmetric space group. The regular arrangement of the crystalline material can be optimized through intermolecular interactions to generate a piezoelectric effect and achieve excellent mechanoluminescence performance. Based on this crystal, a stress visualization response device can be prepared. When writing different letters, the corresponding path information can be clearly displayed. Moreover, the synthesized mechanoluminescent crystals of the present invention show stable luminescence in multiple repeated experiments at low ultrasonic frequencies.
[0024] The beneficial effects of the present invention compared with the prior art: The mechanoluminescent molecules of the present invention are effectively applied to stress detection, ultrasonic luminescence, and underwater ultrasonic detection. The preparation process is simple and the cost is low. This is the first novel mechanoluminescent molecule based on phenoselenazine derivatives, which expands the application range of mechanoluminescent materials. Its phosphorescence efficiency is as high as 61.4%, which is the highest value in the reported mechanoluminescent systems so far. Description of the Drawings
[0025] Figure 1 It is the phosphorescence spectrum of Compound 3 crystals;
[0026] Figure 2 It is the luminescence lifetime diagram of Compound 3 crystals;
[0027] Figure 3 It is the excitation-photoluminescence spectrum of Compound 3;
[0028] Figure 4 It is the luminescence spectrum of Compound 3 crystals under mechanical force;
[0029] Figure 5 It is the piezoelectric amplitude signal generated by Compound 3 crystals in the pressure microscope test;
[0030] Figure 6 It is the piezoelectric phase signal generated by Compound 3 crystals in the pressure microscope test;
[0031] Figure 7 It is a small device prepared based on Compound 3 crystals;
[0032] Figure 8The crystal of Compound 3 produces a luminescence phenomenon at a low ultrasonic frequency;
[0033] Figure 9 It is a schematic diagram of an underwater ultrasonic detection device using the crystal of Compound 3 and the acquisition of the output signal.
[0034] Figure 10 They are the dipole moment values of Compound 1, Compound 2, and Compound 3;
[0035] Figure 11 It is a bar graph of the phosphorescence efficiency of Compound 1, Compound 2, and Compound 3;
[0036] Figure 12 It is the 1H NMR spectrum of Compound 1;
[0037] Figure 13 It is the 13C NMR spectrum of Compound 1;
[0038] Figure 14 It is the 1H NMR spectrum of Compound 2;
[0039] Figure 15 It is the 13C NMR spectrum of Compound 2;
[0040] Figure 16 It is the 1H NMR spectrum of Compound 3;
[0041] Figure 17 It is the 13C NMR spectrum of Compound 3;
[0042] Figure 18 They are the luminescence photos of Compound 3 under ultrasonic excitation at a working frequency of 1 MHz for three repeated experiments;
[0043] Figure 19 It is the luminescence spectrum of the crystal of Compound 1 under mechanical force;
[0044] Figure 20 It is the luminescence spectrum of the crystal of Compound 2 under mechanical force. Specific Embodiments
[0045] The following details the specific embodiments of the present invention. It should be understood that the specific embodiments described herein are only for the purpose of illustrating and explaining the present invention and are not intended to limit the present invention.
[0046] Example 1
[0047]
[0048] Weigh phenoselenazine (0.98 g, 3.98 mmol) and sodium tert-butoxide (0.77 g, 8.01 mmol) and place them in a 100 mL two-necked flask. After sealing, evacuate and refill with nitrogen three times. Subsequently, add 25 mL of N,N-dimethylformamide as the solvent and stir the reaction at room temperature for 2 hours. Then, under nitrogen protection, transfer the mixed solution to a reaction flask containing 2-bromo-4′-fluorobenzophenone (1.17 g, 4.19 mmol) and react at 100 °C for 12 hours. After the reaction is completed, cool the mixture and pour it into water, and extract it three times with dichloromethane. After the extraction solution is evaporated under reduced pressure to remove the solvent, the crude product is separated and purified by column chromatography, and then recrystallized to obtain a pale yellow solid. Finally, dissolve the obtained pale yellow solid in dichloromethane and promote crystal growth by slowly evaporating the solvent to obtain crystals of compound 1 (0.55 g, yield 27.35%). 1 H NMR (400 MHz, CDCl3, ppm): δ 7.67 - 7.56 (m, 7H), 7.42 - 7.21 (m, 7H), 6.91 - 6.87 (m, 2H). 13 C NMR (100 MHz, CDCl3, ppm): δ 194.08, 150.73, 141.47, 140.85, 133.05, 132.60, 132.40, 131.80, 130.66, 128.71, 127.96, 127.74, 127.13, 127.06, 119.48, 112.80.
[0049] As Figure 10 shown, the dipole moment of compound 1 is small. As shown by the mechanoluminescence spectrum of Figure 19 , no luminescence signal can be observed for compound 1, and the mechanoluminescence phenomenon cannot be generated. Compound 1 does not have the mechanoluminescence phenomenon and cannot be used for stress display, ultrasonic devices, and underwater ultrasonic devices.
[0050] Example 2
[0051]
[0052] Weigh phenoselenazine (0.98 g, 3.98 mmol) and sodium tert-butoxide (0.77 g, 8.01 mmol) and place them in a 100 mL two-necked flask. After sealing, evacuate and refill with nitrogen three times. Subsequently, add 25 mL of N,N-dimethylformamide as the solvent and stir the reaction at room temperature for 2 hours. Then, under nitrogen protection, transfer the mixed solution to a reaction flask containing 3-bromo-4′-fluorobenzophenone (1.17 g, 4.19 mmol) and react at 100 °C for 12 hours. After the reaction is completed, cool the mixture and pour it into water, and extract it three times with dichloromethane. After the extract is evaporated under reduced pressure to remove the solvent, the crude product is separated and purified by column chromatography, and then recrystallized to obtain a pale yellow solid. Finally, dissolve the obtained pale yellow solid in dichloromethane and promote crystal growth by slowly evaporating the solvent to obtain crystals of compound 2 (0.61 g, yield 30.33%). 1 1H NMR (400 MHz, CDCl3, ppm): δ 7.84 (t, J = 1.6 Hz, 1H), 7.67 - 7.61 (m, 8H), 7.43 - 7.39 (m, 2H), 7.32 - 7.22 (m, 3H), 6.95 - 6.91 (m, 2H). 13 13C NMR (100 MHz, CDCl3, ppm): δ 193.51, 168.03, 150.22, 141.05, 140.62, 134.53, 132.44, 132.36, 131.79, 129.83, 128.60, 128.27, 128.20, 127.99, 126.99, 122.43, 113.05.
[0053] As Figure 10 shown, compound 2 has a small dipole moment. As shown by the mechanoluminescence spectrum of Figure 20 , no luminescence signal can be observed for compound 2, and it cannot produce mechanoluminescence. Compound 2 does not have mechanoluminescence and cannot be used for stress display, ultrasonic devices, and underwater ultrasonic devices.
[0054] Example 3
[0055]
[0056] Weigh phenoselenazine (0.98 g, 3.98 mmol) and sodium tert-butoxide (0.77 g, 8.01 mmol) and place them in a 100 mL two-necked flask. After sealing, evacuate and refill with nitrogen three times. Subsequently, add 25 mL of N,N-dimethylformamide as the solvent and stir the reaction at room temperature for 2 hours. Then, under nitrogen protection, transfer the mixed solution to a reaction flask containing 4-bromo-4'-fluorobenzophenone (1.17 g, 4.19 mmol) and react at 100 °C for 12 hours. After the reaction is completed, cool the mixture and pour it into water, and extract it three times with dichloromethane. After the extract is evaporated under reduced pressure to remove the solvent, the crude product is separated and purified by column chromatography, and then recrystallized to obtain a pale yellow solid. Finally, dissolve the obtained pale yellow solid in dichloromethane and promote crystal growth by slowly evaporating the solvent to obtain crystals of compound 3 (0.66 g, yield 32.82%). 1 H NMR (400 MHz, CDCl3, ppm): δ 7.67 - 7.55 (m, 10H), 7.43 - 7.39 (m, 2H), 7.25 - 7.22 (m, 2H), 6.94 - 6.91 (m, 2H). 13 C NMR (100 MHz, CDCl3, ppm): δ 194.04, 150.06, 141.09, 137.37, 132.24, 131.75, 131.46, 131.29, 128.57, 128.51, 127.96, 126.93, 126.55, 113.15, 100.00.
[0057] Figure 1 It is the phosphorescence spectrum of the crystals of compound 3. The inset is a photograph of the crystals emitting light under ultraviolet lamp irradiation, verifying that the luminescence property of this material is phosphorescence. Figure 2 It is the luminescence lifetime graph of the crystals of compound 3. As can be seen from the graph, the lifetime is 7.2 ms; Figure 3 It is the excitation-photoluminescence spectrum. From the graph, it can be seen that the compound 3 molecule has a single luminescence center and there are no multiple luminescence centers. Figure 4 It is the luminescence spectrum of the crystals of compound 3 under mechanical force, verifying that the luminescence property is phosphorescence during this process. The inset is a photograph of the crystals emitting light when pressed and broken; Figure 5 It is the piezoelectric amplitude signal generated by the crystals of compound 3 during the pressure microscope test; Figure 6 It is the piezoelectric phase signal generated by the crystals of compound 3 during the pressure microscope test. From the graph, it can be seen that the force-induced luminescence property of this molecule originates from its piezoelectric effect. From Figure 10 it can be seen that the force-induced phosphorescent molecule of compound 3 has a large molecular dipole moment (4.10 Debye). From Figure 11 it can be seen that the phosphorescence efficiency of compound 3 is as high as 61.4%.
[0058] Example 4
[0059] Preparation of composite film based on compound 3 crystal
[0060] Weigh 200 mg of polymer PBAT with a molecular weight of about 120,000 into a 20 mL bottle, and add 2 mL of dichloromethane as a dispersion solvent. After ultrasonic treatment and stirring, a clear solution is obtained. Then weigh 20 mg of the mechanoluminescent crystal powder and add it to the solution, and stir for 0.5 hour to ensure uniform dispersion. Transfer the obtained mixture to a petri dish with a diameter of 3.50 cm, and heat to evaporate dichloromethane, obtaining a composite film with a concentration of 10 wt.%.
[0061] Example 5
[0062] Preparation of stress display device based on compound 3 crystal
[0063] Fill the mechanoluminescent crystal into a quartz groove, and cover its surface with a transparent PET (polyethylene terephthalate) film. Apply pressure with a pen tip to induce the crystal to break and emit light, and the clear light-emitting trajectories of the letters "M" and "L" are successfully recorded by a camera, as shown in Figure 7 , showing the stress path under mechanical force, and confirming the application potential of this material in stress visualization and real-time monitoring.
[0064] Example 6
[0065] Preparation of ultrasonic device based on compound 3 crystal
[0066] Disperse the mechanoluminescent crystal in an oily medium, and use a low-frequency 40 kHz ultrasonic power to excite it. The crystal breaks and emits bright light. As shown in Figure 8 , the compound 3 crystal emits light at a low ultrasonic frequency; thus, it can be seen that the mechanoluminescent crystal can be used in ultrasonic imaging technology. As shown in Figure 18 , when using a 1 MHz ultrasonic power to excite, the crystal breaks and emits bright light, and the bright light emission phenomenon can still be observed after repeating three times.
[0067] Example 7
[0068] Preparation of underwater ultrasonic device based on composite film
[0069] Clamp the composite film prepared in Example 4 between two copper electrodes, and encapsulate it with tape to construct a simple three-layer test device. At a frequency of 10 MHz, this device exhibits excellent time response characteristics (T = 4 μs). As the distance between the probe and the device decreases, the output signal gradually increases, indicating that this device can be used for sound source localization. As shown in Figure 9 , it can be seen that the output signal depends on the different distances between the 10 MHz probe and the device with the composite film.
[0070] Example 8
[0071] The space groups and unit cell parameters of Compounds 1-3 are shown in Table 1 as follows:
[0072] Table 1
[0073]
[0074] As can be seen from Table 1, Compounds 1 and 2 belong to centrosymmetric space groups. It can be seen that the generation of mechanoluminescence requires a non-centrosymmetric space group and a large dipole moment.
[0075] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, and these simple modifications all fall within the protection scope of the present invention.
Claims
1. An organic mechano-phosphorescent material based on phenoselenazine derivatives, characterized in that, The force-induced phosphorescent material has a structure shown in formula (I): Wherein, -X- is one of -O-, -S-, -Se-, -Te- or -SO2-; R1 to R7 are each independently selected from any one of F, Cl, Br, I, -CH3.
2. The force-induced phosphorescent material according to claim 1, wherein The said -X- is selected from one of -O-, -S-, -Se-, -Te- or -SO2-, R1, R2, R4, R5, R6, R7 are each independently selected from -CH3, and the said R3 is selected from any one of F, Cl, Br, I.
3. The mechanoluminescent material according to claim 1, wherein The said -X- is selected from -Se-, R1, R2, R4, R5, R6, R7 are each independently selected from -CH3, and the said R3 is selected from any one of F, Cl, Br, I.
4. The force-induced phosphorescent material according to claim 1, characterized in that The structure of the force-induced phosphorescent material is shown in the following formula:
5. The preparation method of the force-induced phosphorescent material according to claim 4, characterized in that The method comprises the following steps: Weigh phenoselenazine and sodium tert-butoxide and place them in a two-necked flask. After sealing, evacuate and refill with nitrogen. Then add N,N-dimethylformamide as a solvent and stir the reaction at room temperature. Next, under nitrogen protection, transfer the mixed solution to a reaction flask containing 4-bromo-4'-fluorobenzophenone and react at 100 °C. After the reaction is completed, extract with dichloromethane, and then separate and purify by column chromatography to obtain a crude product. Finally, obtain the crystal of the force-induced phosphorescent material by recrystallization.
6. The preparation method of the force-induced phosphorescent material according to claim 5, characterized in that The mixed solution reacts with 4-bromo-4'-fluorobenzophenone for 11 - 13 hours; phenoselenazine and sodium tert-butoxide are stirred and reacted at room temperature for 2 - 3 hours.
7. The preparation method of the force-induced phosphorescent material according to claim 5, characterized in that The molar ratio of phenoselenazine, sodium tert-butoxide to 4-bromo-4'-fluorobenzophenone is 3.9 - 4.1:7.9 - 8.1:4.1 - 4.
2.
8. Use of the organic force-induced phosphorescent material according to claim 1 in stress detection, sonoluminescence and underwater ultrasonic detection.
9. A composite film containing an organic mechanoluminescent material, characterized in that The thin film uses the organic force-induced phosphorescent material according to claim 1 and is prepared by the following method: In poly(butylene adipate-co-terephthalate), add dichloromethane as a dispersion solvent, and obtain a clear solution through ultrasonic treatment and stirring; then weigh the crystal of the force-induced phosphorescent material and add it to the solution, stir to disperse evenly, heat the obtained mixture to volatilize dichloromethane, and obtain a composite thin film in which the polymer coats the force-induced phosphorescent material molecules.
10. The underwater ultrasonic detection composite film according to claim 9, characterized in that The mass ratio of the crystal of the force-induced phosphorescent material to poly(butylene adipate-co-terephthalate) is 1:10 - 11.